Modified Poly(lactic-co-glycolic acid) Nanoparticles for Enhanced Cellular Uptake and Gene Editing in the Lung - Fields, Rachel J. (Adv Healthc Mater, 2014)
Modified nanoparticles composed of a blend between poly(β-amino ester) (PBAE) and poly(lactic-co-glycolic acid) (PLGA), surface coated with cell-penetrating peptides (CPPs), have previously shown promise in gene delivery. In this study, we sought to evaluate pulmonary cellular uptake of these modified nanoparticles, and demonstrate their potential as vectors in pulmonary gene therapy. This work shows that surface modified PLGA/PBAE/CPP nanoparticles achieve higher cellular association than traditional nanoparticles composed of PLGA or PLGA/PBAE blends alone.